Detailed Review of Type-2 Diabetes Mellitus (T2DM) and Its Prevalence - Abdulkadhm, Mohammed Mustafa (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes Mellitus is considered as a group of common disorders that shares the phenotype of hyperglycemia. The world is facing various challenges in diabetes management, such as a rising proportion in various countries. As fast as the socioeconomic changes occurring in the rural as well as areas, the prevalence of type-2 diabetes are found to increase several fold which is thereby responsible for early morbidity and mortality in the population. The difference in Urban-Rural prevalence of type-2 diabetes is leading to urbanization and transformation in life style due to Western Culture adoption is spreading widely. In this paper we have presented the detailed review of type-2 diabetes prevalence in urban and rural areas. The screening and awareness events for the general population have to be organized by the Government to achieve prevention and better cure of type-2 diabetes.